The Effect of Vegetation Density on The Total Suspended Solid (TSS) Concentration in The Aquatic Area of Pomalaa District - Barus, Mika Debora Br.; Sofyan A. P., Andi Baso; Artati, Yuniar; Kharisma, Gaby Nanda; Maulana, Achmad Zidane (Universitas Lambung Mangkurat, 2023)
Analysis of the influence of vegetation density levels on the concentration of Total Suspended Solids (TSS) in aquatic areas is crucial in the Pomalaa District, an area characterized by extensive mining activities. This research aims to examine changes in vegetation density conditions and analyze the influence of vegetation density levels on TSS concentrations in the aquatic region. Changes in vegetation density conditions are analyzed through multi-temporal remote sensing image processing using the NDVI method. The TSS concentration is analyzed using the gravimetric method. Meanwhile, the influence of vegetation density level on TSS concentration is analyzed using the Pearson correlation coefficient equation. The results of the research show that there has been an increase in the area with very low levels of vegetation density and a decrease in the area with high levels of vegetation density in the period 2014 to 2023. The calculated results of TSS concentrations at the research location are 78 mg/l to 111 mg/l. The correlation analysis shows that the broader the area with very low vegetation density, the higher the TSS concentration in the aquatic environment. Additionally, the larger the area with high vegetation density, the lower the TSS concentration value of the water at the research locations.